Pengaruh Love of Money, Sanksi Pajak dan Pemahaman Pajak terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan di Kecamatan Medan Johor - Jihan Tazkiyah Sungkar (Fakultas Ilmu Sosial Dan Humaniora, Universitas Ibbi, 2025)
This study aims to examine the influence of love of money, tax sanctions, and tax understanding on taxpayer compliance in paying Land and Building Tax in district of Medan Johor. The research method is quantitative with survei using questionnaires. The population used in this study was the payer of Land and Building Tax in Medan Johor 2023, totaling 25,371 individuals. The sampling technique was cluster sampling, so the sample used was 370 respondents. The method of data collection was the distribution of questionnaires with a Likert scale. The results of the study indicate that love of money has a significantly negative effect on taxpayer compliance, while tax sanctions and tax understanding have a significantly positive effect on taxpayer compliance. Simultaneously, love of money, tax sanctions, and tax understanding have a significant effect on taxpayer compliance.